A Narrative Review: The Day-Case Surgery Model: Maximizing Efficiency, Safety, and Patient Satisfaction - Albalawi, Suoad; Ashwag Mohammed Alasmarei; Anwar Ali Alzahrani; Fahad Ali Alshamrani; Yahya Ebrahim Mohammad Hamedi; Mohammed Fulayyih Marshad Alsharifi; Khairat Majrshi; Zahra Mohammed Ahmed Alhazmi; Ohud Nawi Sukhayl Alruwaili; ‏Mohammed Hathal Thunayyan Alotaibi; Meshal Muidh Nawahi A Mutiri; Bader Ibrahim Al Dayel; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The day-case (ambulatory) surgery model represents a cornerstone of modern healthcare delivery, shifting appropriate surgical procedures from inpatient to same-day discharge settings. This transition demands flawless system engineering and interdisciplinary coordination to ensure patient safety, optimize resource utilization, and maintain high satisfaction. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review aims to synthesize current evidence on the operational, clinical, and human factors required for a successful day-case surgery program. It will analyze the integrated roles of pharmacy, surgery, nursing, radiology, laboratory, medical administration, and health security. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature search was conducted in PubMed, CINAHL, and Scopus (2010-2024) for peer-reviewed articles, reviews, and clinical guidelines about ambulatory surgery efficiency, safety protocols, and interdisciplinary coordination. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Success hinges on meticulous pre-operative optimization, standardized clinical pathways, and seamless intraoperative coordination. Critical elements include patient selection, procedure-specific analgesia, streamlined ancillary services, and rigorous discharge criteria managed by nursing. Administrative efficiency and robust infection control are foundational to system performance. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The day-case model is a viable, safe, and cost-effective standard for numerous procedures. Its success is not serendipitous but the product of deliberate system design, requiring unwavering collaboration across all seven defined fields to create a patient journey that is efficient, secure, and satisfactory.